Writing a viable research proposal: an appraisal - Ansari, Abdul Haseeb; Jamal, Parveen; Ahmad, Muhamad Hassan (Satyam Law International, 2019)
Be it academic, industrial or administrative, a continued research process is a tool of salubrious development. The chapter sheds some light on making a good and viable research proposal.